Perubahan Sosial Masyarakat Suku Baduy Luar sebagai Akibat Modernisasi - Aprianti, Syapri; Putri Indriyanti, Ade; Novianti Lestari, Putri; Nur Fatihah, Murnia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is an area with thousands of islands scattered with different characteristics, resulting in a diverse range of ethnicities and cultures. The customs, culture, and traditions of the Indonesian people are always evolving with the times. Modernization aims to create a prosperous society and is a cause of social and cultural change. It is a process of transitioning from traditional to more advanced or modern ways of living. However, not all regions prioritize modernization and forget their traditions. This is evident in some areas of Indonesia that still preserve their customs and culture from outside influences and modernization. For example, the Baduy tribe in the Lebak Regency, Banten, which still maintains and preserves their original culture. The rapid development of modernization has also impacted the Baduy tribe, particularly the Outer Baduy community. The purpose of this writing is to explain the influence of modernization on the Outer Baduy tribe using the Literature Study Method.